L’implantation des gares TGV en France : tensions interscalaires, jeux d’acteurs et recompositions spatiales - Valérie Facchinetti-Mannone; Jean-Jacques Bavoux (Belgeo)
The expansion of the high-speed rail network revives the question of optimal location for train stations, especially in France, where a logic of efficiency favours frequent scheduled trips between major cities at the expense of intermediary spaces. This option has induced two types of location: a central main station for larger cities and a peripheral station for mid-size ones. These choices are the result of interactive processes involving all levels of spatial organization. Examining the decision processes that have led to the location of TGV stations in France, we see that the choices and the valorization strategies induced result from the combination of variable elements according to the specificities of covered territories and players’ strategies. Most of the locations retained are the result of power struggles between national, regional and local territorial logics of the decision-makers.